Relationships among peri-traumatic circulating endocannabinoids and long-term, negative outcomes following traumatic injury - Emily A. Albertina; Carissa W. Tomas; Timothy J. Geier; Sydney C. Timmer-Murillo; Isela G. Pina; Kelley Jazinski-Chambers; Garrett Sauber; Jacklynn M. Fitzgerald; Christine L. Larson; Terri A. deRoon-Cassini; Cecilia J. Hillard (Psychopharmacology, 2026)
Rationale Traumatically injured individuals can develop chronic negative psychological sequelae. Improved understanding of contributing, peri-traumatic risk factors is essential to reduce the risk of these consequences. Previous studies have found that peri-traumatic, circulating endocannabinoid concentrations are positively associated with development of post-traumatic stress disorder (PTSD), chronic pain and depression months later, particularly in members of racial/ethnic groups that have been historically marginalized. Objectives This replication study examined relationships among peri-trauma serum endocannabinoid concentrations and long-term consequences in a cohort comprised primarily of individuals from marginalized racial and ethnic groups. Methods Participants ( n = 100; 81% from marginalized racial and ethnic groups) were traumatically injured adults presenting to the ED of an urban tertiary care hospital. Endocannabinoids N -arachidonoylethanolamine (AEA) and 2-arachidonoylglycerol (2-AG) were measured in serum collected within days (peri-trauma) and 6–10 months following injury (follow-up). Assessments, including PTSD, depression, pain and quality of life were completed. Statistical approaches, including multivariate, hierarchical regressions, were used to determine associations among serum endocannabinoid concentrations and long-term outcomes. Results Although it did not survive correction for multiple comparisons, peri-trauma serum 2-AG concentrations. Peri-trauma serum 2-AG concentrations were also positively associated with PTSD, pain severity, and functional engagement scores at follow-up. There were no significant associations between circulating 2-AG or AEA and depression. Conclusions These findings generally replicate earlier studies demonstrating that serum 2-AG concentrations are biomarkers of risk for PTSD and pain and uncover an additional association with poor functional quality of life. Further studies are needed to determine the underlying mechanisms of these relationships.

Kynurenine pathway dysregulation via loss of QPRT drives declines in activity and altered metabolism in mice - Reyhan Westbrook; Vinal Menon; Joy Cagmat; Timothy Garrett; Robert Schwarcz; Jeremy Walston; Peter M. Abadir; Tae Chung (GeroScience, 2025)
Chronic inflammatory pathway activation increases with age and is epidemiologically linked to multiple aging-related pathophysiological processes, phenotypes such as physical frailty and sarcopenia and early healthspan declines in aging organisms. Despite this, molecular mechanisms that directly connect chronic inflammation to these conditions remain poorly characterized. We hypothesize that chronic inflammation contributes to the development of age-related phenotypes by increasing the degradation of dietary tryptophan into multiple metabolites with unique physiological properties, called kynurenines, via the ‘kynurenine pathway’ (KP). To understand the impact of elevated KP metabolites on mammalian healthspan we utilized the quinolinate phosphoribosyltransferase knock-out (QPRT −/− ) mouse which lacks the terminal enzyme of the KP and thus develops increased levels of downstream kynurenines. We tested the effects of this mutation on glucose handling, spontaneous motor activity, body composition and metabolism using indirect calorimetry, in male and female, young, middle aged and older mice. QPRT − / − mice had significantly altered levels of numerous KP metabolites and nicotinamide. Phenotypic characteristics varied in a sex-specific manner with decreased activity, lean mass and VO 2 , and impaired glucose clearance as early as 12 months seen in female QPRT −/− compared to age and sex-matched mice. Male QPRT −/− mice developed reduced lean mass by middle age and had altered respiration and food intake. This data indicates that KP dysregulation can drive declines in activity and alter metabolism in mammals and is a potential target to intervene on frailty and functional decline.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Allee effects introduced by density dependent phenology - Timothy J. Pervenecki; Sharon Bewick; Garrett Otto; William F. Fagan; Bingtuan Li (Mathematical Biosciences, 2024)

A ∼200-year relative sea-level reconstruction from the Wellington region (New Zealand) reveals insights into vertical land movement trends - Daniel J. King; Rewi M. Newnham; Andrew B.H. Rees; Kate J. Clark; Ed Garrett; W. Roland Gehrels; Timothy R. Naish; Richard H. Levy (Marine Geology, 2024)

Monitoring spore washoff during a biological contamination incident response using automated stormwater samplers and sensors to predict contamination movement - Anne M. Mikelonis; John Hall; Chris A. Dunn; Timothy McArthur; Garrett Wiley; Chelsea L. Hintz; Joshua Steenbock; Shannon Serre; Michael Worth Calfee; Michael Pirhalla (Science of The Total Environment, 2023)

Relating storm-snow avalanche instabilities to data collected from the Differential Emissivity Imaging Disdrometer (DEID) - Travis J. Morrison; Trent Meisenheimer; Timothy Garrett; Dhiraj Singh; Spencer Donovan; Eric Pardyjak (Cold Regions Science and Technology, 2023)

In situ digital holographic microscopy for rapid detection and monitoring of the harmful dinoflagellate, Karenia brevis - Ranjoy Barua; Delaney Sanborn; Lisa Nyman; Malcolm McFarland; Timothy Moore; Jiarong Hong; Matt Garrett; Aditya R. Nayak (Harmful Algae, 2023)

Rapid Treatment with Intramuscular Magnesium Sulfate During Cardiopulmonary Resuscitation Does Not Provide Neuroprotection Following Cardiac Arrest - Rui Zhang; Timothy D. Bryson; Garrett M. Fogo; Jinhui Liao; Sarita Raghunayakula; Jennifer Mathieu; Joseph M. Wider; Xiaodan Ren; Kathleen J. Maheras; Katlynn J. Emaus; Erin Gruley; Yuguo Chen; et al. (Molecular Neurobiology, 2022)

Application of carbon nanotubes for removal of emerging contaminants of concern in engineered water and wastewater treatment systems - Sudarshan Kurwadkar; Timothy V. Hoang; Kailas Malwade; Sushil R. Kanel; Willie F. Harper; Garrett Struckhoff (Nanotechnology for Environmental Engineering, 2019)

An individual-based model of chaparral vegetation response to frequent wildfires - Timothy A. Lucas; Reanna A. Doña; Wancen Jiang; Garrett C. Johns; Dayna J. Mann; Cassandra Seubert; Noah B. C. Webster; Charlotte H. Willens; Stephen D. Davis (Theoretical Ecology, 2017)

Involvement of a caleosin in lipid storage, spore dispersal, and virulence in the entomopathogenic filamentous fungus, B eauveria bassiana - Yanhua Fan; Almudena Ortiz‐Urquiza; Timothy Garrett; Yan Pei; Nemat O. Keyhani (Environmental Microbiology, 2015)
Summary Eukaryotic cells store lipids in membrane‐encased droplets. The entomopathogenic fungus, B eauveria bassiana , initiates infection via attachment of its spores to the epicuticle or waxy layer of target insects, degrading and assimilating host surface hydrocarbons, carbohydrates and proteins. Caleosins are components of the proteinaceous coat of lipid droplets and a single B . bassiana caleosin homologue, B bcal1 , was identified and characterized. The BbCal1 sequence contained an EF ‐hand C a 2+ binding domain and potential hydrophobic stretches similar to those found in plant caleosins, along with a proline knot motif defined by only two proline residues. Targeted gene inactivation of B bcal1 did not appear to affect spore germination, growth on lipid substrates or stress response, but changes in lipid, vacuole and endoplasmic reticulum/multilamellar vesicle‐like structures, and altered cellular lipid profiles were seen in conidia grown on a variety of substrates including potato dextrose agar, olive oil, glyceride trioleate, oleic acid and the alkane, C 16 . The Δ B bcal1 mutant produced more compact assemblages of conidia, displayed a reduced and delayed spore dispersal phenotype, and showed decreased virulence in insect bioassays using the greater wax moth, G alleria mellonella . Our data indicate novel functions for caleosins in fungal virulence, spore development and the trafficking and/or turnover of lipid‐related structures.

Priority research questions for the UK food system - John S. I. Ingram; Hugh L. Wright; Lucy Foster; Timothy Aldred; David Barling; Tim G. Benton; Paul M. Berryman; Charles S. Bestwick; Alice Bows-Larkin; Tim F. Brocklehurst; Judith Buttriss; John Casey; et al. (Food Security, 2013)
The rise of food security up international political, societal and academic agendas has led to increasing interest in novel means of improving primary food production and reducing waste. There are however, also many ‘post-farm gate’ activities that are critical to food security, including processing, packaging, distributing, retailing, cooking and consuming. These activities all affect a range of important food security elements, notably availability, affordability and other aspects of access, nutrition and safety. Addressing the challenge of universal food security, in the context of a number of other policy goals (e.g. social, economic and environmental sustainability), is of keen interest to a range of UK stakeholders but requires an up-to-date evidence base and continuous innovation. An exercise was therefore conducted, under the auspices of the UK Global Food Security Programme, to identify priority research questions with a focus on the UK food system (though the outcomes may be broadly applicable to other developed nations). Emphasis was placed on incorporating a wide range of perspectives (‘world views’) from different stakeholder groups: policy, private sector, non-governmental organisations, advocacy groups and academia. A total of 456 individuals submitted 820 questions from which 100 were selected by a process of online voting and a three-stage workshop voting exercise. These 100 final questions were sorted into 10 themes and the ‘top’ question for each theme identified by a further voting exercise. This step also allowed four different stakeholder groups to select the top 7–8 questions from their perspectives. Results of these voting exercises are presented. It is clear from the wide range of questions prioritised in this exercise that the different stakeholder groups identified specific research needs on a range of post-farm gate activities and food security outcomes. Evidence needs related to food affordability, nutrition and food safety (all key elements of food security) featured highly in the exercise. While there were some questions relating to climate impacts on production, other important topics for food security (e.g. trade, transport, preference and cultural needs) were not viewed as strongly by the participants.

Are there basic physical constraints on future anthropogenic emissions of carbon dioxide? - Timothy J. Garrett (Climatic Change, 2011)

Poisoning hospitalization correlates with poison center call frequency - Timothy E. Albertson; R. Steven Tharratt; Kathy Marquardt; Judith Alsop; John K. Ninomiya; Garrett E. Foulke (Journal of Medical Toxicology, 2008)